Pengaruh Tren Pencarian Google terhadap Preferensi Konsumen Asuransi Syariah dan Konvensional di Indonesia - Hafshoh Hafidzoh; Yayan Satyakti (Journal of Islamic Economics and Finance, 2025)
The insurance penetration rate in Indonesia remains relatively low, despite the important roles of both conventional and sharia insurance in mitigating unexpected financial risks. As a Muslim-majority country, consumer preferences for insurance models aligned with personal values represent a crucial concern, yet are still rarely explored using actual behavioral data. This study aims to examine the influence of Google search trends on consumer preferences in choosing between sharia and conventional insurance in Indonesia. The research applies binary logistic regression using a combination of primary data (questionnaire) and secondary data (Google Trends). Respondents were purposively selected based on stable economic status and prior experience in searching for insurance information. The results reveal that search trends significantly influence preferences for sharia insurance, but not for conventional insurance. Furthermore, religiosity and its interaction with search trends also significantly affect preferences for both insurance models. These findings contribute to big data-based consumer research and offer strategic implications for academics, industry stakeholders, and regulators in enhancing insurance literacy and participation in Indonesia..